Teaching Tuvan Language to Japanese Learners - Sawada, Kaori; Kurosawa, Katsuhiko (The New Research of Tuva, 2018)
One author of this article (Kaori Sawada) lived in the Republic of Tuva and studied Tuvan throat singing (xöömei) and Tuvan language from 2011 to 2017. She is an interpreter between Tuvan and Japanese languages, currently teaching Tuvan in Japan. The fans of Tuvan culture in Japan are holding their interests since 2011, however, the numbers of Japanese people making their efforts to study Tuvan language are few. The purpose of this article is to discuss the problems and the reactions of the students during the teaching practices of Tuvan language in Japan and to share our opinions, referring to this author’s experience of studying Tuvan language in the Tuvan State University, about the solution of the problems, effective systems and learning materials. The article also presents the outcomes of a survey of Japanese studying Tuvan language. The questionnaire-based survey was held in December 2017 on Facebook aimed to clarify some of the complexities faced by Japanese students of Tuvan. Of the 8 respondents, all were fans of xöömei and musicians who were highly interested in Tuvan culture. They could be seen as potential popularizers of Tuvan culture in Japan. The authors provide examples of difficulties the Japanese students of Tuvan can face and explain the reasons for these problems. The article concludes with a number of practical recommendations on how to make teaching Tuvan language to Japanese learners more efficient.